Sertipikat Elektronik dalam Kebijakan Satu Peta dan Satu Data: Reformasi Digital Sistem Pertanahan di Indonesia - Ernandyanti, Della; Suparjo, Suparjo (Universitas Batanghari Jambi, 2026)
This research aims to analyze the role of the One Map Policy and the One Data Policy in enhancing the validity and accuracy of data for the issuance of electronic land certificates, as well as to examine how the implementation of electronic certificates contributes to improving legal certainty and the protection of land rights in Indonesia’s digital era. Using a doctrinal research approach supported by secondary data, including laws and regulations, books, journals, and articles, this study finds that the One Map Policy provides an integrated and standardized geospatial data foundation that ensures spatial accuracy in electronic certificates. Meanwhile, the One Data Policy ensures the consistency and validity of data related to rights holders and ownership history. The combination of these two policies is essential to creating credible electronic certificates and reducing the potential for future disputes. Furthermore, the study identifies that the implementation of electronic certificates can improve the efficiency and transparency of land administration services, thereby strengthening legal certainty and protecting land rights from risks of loss, damage, and forgery. Nevertheless, challenges such as the digital divide, the need for data harmonization, and regulatory refinement must be addressed to optimize the implementation of the electronic certificate system across Indonesia.